Extracellular serine proteases by Acremonium sp. L1-4B isolated from Antarctica: Overproduction using cactus pear extract with response surface methodology. Issue 4 (October 2015) - Nascimento, Talita Camila Evaristo da Silva; Sena, Amanda Reges de; Gomes, José Erick Galindo; Santos, Wellington Leal dos; Agamez Montalvo, Gualberto Segundo; Tambourgi, Elias Basile; Medeiros, Erika Valente de; Sette, Lara Durães; Pessoa Junior, Adalberto; Moreira, Keila Aparecida
Abstract: Acremonium sp. L1-4B isolated from lichen in Antarctica was used to produce extracellular proteases through submerged fermentation using cactus pear extract ( Opuntia ficus-indica Mill.). A 2 3 factorial design was applied to optimize the protease production using three independent variables, namely temperature, pH and concentration of yeast extract, was also used a Central Composite Design (CCD) under Response Surface Methodology (RSM). All variables and interactions analyzed in the factorial design were significant or marginally significant, a Central Composite Design was developed, and the Response Surface Methodology towards the highest point it was established. The experimental model was validated under 14 °C, pH 7.54, and 0.55% yeast extract, showing a protease activity of 447.65±2.6 U/mL by a prediction model of 445.48 U/mL. The enzyme showed a molecular weight of 59 kDa; it was inhibited in the presence of PMSF (serine protease); it presented optimal conditions at pH 8.0 and 50 °C; it remained stable at pH in the 3.0–9.0 range and between 10 and 40 °C; it showed a tolerance to 3000 mM NaCl as well as to surfactants, hydrogen peroxide and urea at 5%. This paper presents a proposal for an economically attractive production methodology using cactus pear as a primary source of carbon. In addition, the protease secreted by Acremonium sp. L1-4B presented a combination of biochemical characteristics that grants a promising variability of biotechnological applications. Graphical abstract: Highlights: Attractive method proposal on cactus pear biotransformation. Feasibility of agricultural products use in bioprocesses. Cold-active protease secreted by filamentous fungus isolated in Antarctica. Different NaCl and surfactants concentrations tolerant biocatalyst. Serino protease stable on all evaluated pH ranges.